1, 10-Phenanthroline-based periodic mesoporous organosilica: from its synthesis to its application in the cobalt-catalyzed alkyne hydrosilylation. Issue 12 (9th March 2023) - Lin, Xiao-Tao; Ishizaka, Yusuke; Maegawa, Yoshifumi; Takeuchi, Katsuhiko; Inagaki, Shinji; Matsumoto, Kazuhiro; Choi, Jun-Chul
Abstract : A 1, 10-phenanthroline-based periodic mesoporous organosilica (Phen-PMO) with an ordered 2-D hexagonal mesoporous structure was synthesized by co-condensation of 3, 8-bis[(triisopropoxysilyl)methyl]-1, 10-phenanthroline and BTEE. Abstract : 1, 10-Phenanthroline (Phen) is a typical ligand for metal complexation and various metal/Phen complexes have been applied as a catalyst in several organic transformations. This study reports the synthesis of a Phen-based periodic mesoporous organosilica (Phen-PMO) with the Phen moieties being directly incorporated into the organosilica framework. The Phen-PMO precursor, 3, 8-bis[(triisopropoxysilyl)methyl]-1, 10-phenanthroline (1a ), was prepared via the Kumada–Tamao–Corriu cross-coupling of 3, 8-dibromo-1, 10-phenanthroline and [(triisopropoxysilyl)methyl]magnesium chloride. The co-condensation of 1a and 1, 2-bis(triethoxysilyl)ethane in the presence of P123 as the template surfactant afforded Phen-PMO 3 with an ordered 2-D hexagonal mesoporous structure as confirmed by nitrogen adsorption/desorption measurements, X-ray diffraction, and transition electron microscopy. Co(OAc)2 was immobilized on Phen-PMO 3, and the obtained complex showed good catalytic activity for the hydrosilylation reaction of phenylacetylene with phenylsilane.